New trends in the study of post-transplant acute kidney injury after liver transplantation - I. M. Iljinsky; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
Acute kidney injury (AKI) after liver transplantation (LT) is a pressing issue and remains the focus of many researchers. The etiology of AKI is multifactorial, but the main one is ischemia-reperfusion injury to the liver transplant. Numerous preoperative, intraoperative and postoperative risk factors contribute to the development of AKI. The use of standard classifications, such as AKIN, RIFLE and KDIGO, has improved post-transplant AKI diagnosis. However, determination of creatinine levels in the blood enables AKI diagnosis only in the later stages of this syndrome. Therefore, studies are currently underway to find ways of early diagnosis of AKI using biomarkers. Transition to a molecular level not only improves accuracy but also facilitates early diagnosis of AKI. Currently, the diagnostic capabilities of neutrophil gelatinase-associated lipocalin (NGAL) are the most investigated. To date, there are no known measures of preventing post-transplant AKI. Moreover, treatment of this condition cannot be considered satisfactory. Even a mild post-transplant AKI can be fatal. In severe AKI, where renal replacement therapy is used, there is a risk of death in the intensive care unit. More than half of AKI patients develop chronic kidney disease requiring chronic hemodialysis.